Idiosyncratic responses to simulated herbivory by root fungal symbionts in a subarctic meadow - Kytöviita, Minna-Maarit; Olofsson, Johan (Arctic, Antarctic, and Alpine Research, 2021)
Plant-associated fungi have elementary roles in ecosystem productivity. There is little information on the interactions between arbuscular mycorrhizal (AM) fungal symbiosis, fine endophytic (FE) and dark septate endophytic (DSE) fungi, and their host plants in cold climate systems. In particular, the environmental filters potentially driving the relative abundance of these root symbionts remain unknown. We investigated the interlinkage of plant and belowground fungal responses to simulated herbivory (clipping, fertilization, and trampling) in a subarctic meadow system. AM and FE frequency in the two target plant roots, Potentilla crantzii and Saussurea alpina, was unaffected by simulated herbivory, highlighting the importance and resilience of arbuscule forming mycorrhizas in a range of environmental conditions. Fertilization and trampling increased DSE colonization in P. crantzii roots although generally P. crantzii performance was reduced in these plots. The idiosyncratic responses by DSE fungal frequency in the two host plants in our experiment indicate that the host plant identity has a pivotal role in the DSE fungus–plant outcome. DSE fungal frequency did not respond to environmental manipulations in a manner similar to arbuscular mycorrhizas, suggesting that they have a different role in plant ecology.